THE FUNCTIONAL ROLE OF FI’IL MUḌĀRI’ I’RĀB IN THE QUR’AN: A SEMANTIC ANALYSIS OF SURAH AN-NĀZI’ĀT - Saleh; Yazid Abdul Aziz; Agung Pranoto Kadiatmaja (Al Ibrah: Journal of Arabic Language Education, 2026)
This study examines the functional role of fi'il muḍāri' i'rāb in Surah An-Nāzi'āt through an integrated naḥw-tafsīr framework. Previous studies tend to treat i'rāb as a purely formal grammatical category, detached from semantic interpretation, while exegetical studies often overlook grammatical precision. This study addresses that gap by demonstrating that i'rāb is not merely a syntactic marker but an active constituent of Qur'anic meaning. Using a qualitative library research method with a descriptive-analytical approach, the study identifies thirteen fi'il muḍāri' forms in the surah, classified across three i'rāb categories: marfū', manṣūb, and majzūm. The analysis reveals a clear correlation between each inflectional form and its semantic function within the surah's eschatological discourse. The marfū' form, which constitutes 84.6% of the identified forms, operates through istiḥḍār al-ḥāl, rendering future and past events as vivid, immediate realities for the reader. The manṣūb form encodes gradual spiritual transformation within a non-confrontational da'wah strategy. The majzūm form compresses and relativizes worldly time, reinforcing the surah's affirmation of the Hereafter's certainty. These findings demonstrate that the integrated naḥw-tafsīr framework is analytically productive and replicable for examining how grammatical form shapes Qur'anic meaning across different surahs.تتناول هذه الدراسة الوظيفةَ الدلاليةَ لإعراب الفعل المضارع في سورة النازعات، وذلك من خلال إطار منهجي تكاملي يجمع بين علم النحو وعلم التفسير. وقد دأبت الدراسات السابقة على معالجة الإعراب بوصفه ظاهرةً نحويةً شكليةً مجردةً من أبعادها الدلالية، في حين تغفل الدراسات التفسيرية في الغالب عن الدقة النحوية. وتسعى هذه الدراسة إلى ردم هذه الفجوة، بإثبات أن الإعراب لا يُعدّ مجرد علامة تركيبية، بل هو ركيزة فاعلة في تشكيل المعنى القرآني. واتبع البحث المنهج الوصفي التحليلي في إطار الدراسة المكتبية النوعية، وقد رُصد في السورة ثلاثة عشر فعلاً مضارعاً، صُنِّفت وفق ثلاث حالات إعرابية: الرفع، والنصب، والجزم. وتكشف نتائج الدراسة عن ارتباط وثيق بين كل صيغة إعرابية ووظيفتها الدلالية في السياق الأخروي للسورة. فالمرفوع، الذي يمثل ٨٤،٦% من الأفعال المرصودة، يُحقق معنى استحضار الحال، إذ يُقرِّب الأحداث الماضية والمستقبلية إلى وعي المتلقي ويجعلها حاضرةً أمامه. أما المنصوب فيُجسّد مسيرة التحول الروحي التدريجي ضمن أسلوب دعوي غير مواجِه. وأما المجزوم فيُقلِّص الزمن الدنيوي ويُنسِّبه، مُعززاً يقينَ الآخرة الذي تقوم عليه السورة. وتُثبت هذه النتائج مجتمعةً أن الإطار التكاملي بين النحو والتفسير منهجٌ ناجعٌ وقابلٌ للتطبيق في دراسة العلاقة بين الصيغة النحوية والمعنى القرآني عبر سور متنوعة.